Antonymy : a corpus based perspective - Jones, Steven, 1974- (Routledge advances in corpus linguistics., 2002)
Antonymy is the technical name used to describe 'opposites', pairs of words such as rich/poor, love/hate and male/female. This book provides a detailed and comprehensive account of the phenomenon.